Changes in mangrove coverage in Culebra Bay, North Pacific of Costa Rica (1945-2010). - Benavides Varela, Catalina; Samper Villarreal, Jimena; Cortés, Jorge (Revista de Biología Tropical, 2016)
Despite the economic and environmental services that mangroves provide, they continue to be threatened by overexploitation, pollution, and land use change. Costa Rica has mangrove areas on the Pacific and Caribbean coasts, and cover has been declining since the 1980s. However, data on mangrove coverage are not continually updated and are often based on inaccurate estimates. It is therefore necessary to assess the current extension and variation of the mangrove cover in recent years, to determine changes. The mangrove cover was analyzed in two mangrove forests located in Bahía Culebra, North Pacific: Iguanita and Playa Panamá. For this, aerial photographs and satellite imagery were used to study changes for a 65 year period (1945-2010). Spatio-temporal changes were found in mangroves coverage, and adjacent forests and areas without vegetation. Lower mangrove cover occurred during the 1970s (28.4 ha in Iguanita and 4.8 ha in Playa Panamá); but increased in recent years (38.9 ha in Iguanita and 12.0 ha in Panamá). Changes in forest cover by the Iguanita and Playa Panama mangroves were related to the history of land use around Bahía Culebra. Before 1980, there was extensive and intensive cattle ranching, increasing the deforestation rate; after that year, these practices were abandoned and secondary forest coverage increased until 2000. To ensure the adequate protection of mangroves, it is not only important to protect mangrove forests, but it is also necessary to establish buffer zones on their surroundings, to mitigate and/or reduce possible impacts.